2015
DOI: 10.1097/dss.0000000000000500
|View full text |Cite
|
Sign up to set email alerts
|

The Demographics and Rates of Tattoo Complications, Regret, and Unsafe Tattooing Practices

Abstract: Given the rates of pruritic tattoos and tattoo regret, there is an opportunity, and trust among people with tattoos, for dermatologists to manage these complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 17 publications
1
43
1
Order By: Relevance
“…Despite this distinction, the Add Health survey asks only a single question in this area—whether the respondent has a permanent tattoo. Convenience samples are pervasive in the tattoo literature (e.g., 998 university students in King and Vidourek, 551 people walking through New Orleans).…”
Section: Methodsmentioning
confidence: 99%
“…Despite this distinction, the Add Health survey asks only a single question in this area—whether the respondent has a permanent tattoo. Convenience samples are pervasive in the tattoo literature (e.g., 998 university students in King and Vidourek, 551 people walking through New Orleans).…”
Section: Methodsmentioning
confidence: 99%
“…Not all tattoos have deep symbolic meaning . Some are obtained on a whim or a dare or while the person obtaining the tattoo is inebriated or otherwise impaired . Some images are chosen simply as a pleasing design, although even these reflect individual aesthetic and cultural values.…”
Section: Psychosocial Considerationsmentioning
confidence: 99%
“…Regret is a common complication of tattooing . Up to 50% of individuals with a tattoo develop reservations about their art, and more than 20% desire removal but are inhibited by cost and potential side effects .…”
Section: Tattoo Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Instead, people with tattoo-related complications often seek help from tattoo artists. A recent survey showed that approximately 93% of tattooed individuals perceived tattooists as either ‘knowledgeable' or ‘very knowledgeable' about tattoo-related infections and allergies [8]. A study of tattooed adolescents reported that teens prefer to seek tattoo-related medical advice from commercial tattoo artists rather than physicians [9].…”
Section: Introductionmentioning
confidence: 99%